Cracking the organic chemistry: unleashing precision learning with smart questions in ChatGPT - Antypenko, O. M.; Antypenko, L. M.; Антипенко, Олексій Миколайович (My University, 2024)
The path to mastering any subject becomes an exciting adventure to strategically unravel its complexities through a variety of thoughtprovoking questions.